The use of phenomenographic approach to investigate students’ conceptions of the use of web 2.0 tools (2010)
This paper discusses the data collection instrument and data analysis using phenomenography, a qualitative research approach used to investigate DILL students’ conceptions of the use of Web 2.0 tools. The research was undertaken as researcher’s master’s thesis in the digital library learning programme at the Institute of Information Studies, Tallinn University. The iterative process of phenomenography research specialization and justification for its use for the current study are discussed.